Metabolic profiles associated with exposure to ambient particulate air pollution: findings from the Betula cohort - Raza, Wasif; Öhman, Anders; Kanninen, Katja M.; Jalava, Pasi; Zeng, Xiao-wen; de Crom, Tosca O. E.; Ikram, M. Arfan; Oudin, Anna (Frontiers in Public Health, 2024)
Air pollution is a significant contributor to morbidity and mortality globally and has been linked to an increased risk of dementia. Previous studies within the Betula cohort in Northern Sweden have demonstrated associations between air pollution and dementia, as well as distinctive metabolomic profiles in dementia patients compared to controls. This study aimed to investigate whether air pollution is associated with quantitative changes in metabolite levels within this cohort, and whether future dementia status would modify this association. Both short-term and long-term exposure to air pollution were evaluated using high spatial resolution models and measured data. Air pollution from vehicle exhaust and woodsmoke were analysed separately. Metabolomic profiling was conducted on 321 participants, analyzing 58 serum samples from dementia patients and a control group matched for age, sex, and education level using nuclear magnetic resonance spectroscopy. While no statistically significant associations were found between any metabolites and any measures of short-term or long-term exposure to air pollution, there were trends potentially suggesting associations between both long-term and short-term exposure to air pollution with lactate and glucose metabolites. Notably, these associations were observed despite the lack of correlation between long-term and short-term air pollution exposure in this cohort. There were furthermore tendencies for associations between air pollution from wood-smoke to be more pronounced in participants that would later develop dementia, which may suggest an effect depending on urban/rural factors. While these findings provide some new insights into the link between air pollution and metabolic markers in a low-exposure setting, addressing existing limitations is crucial to improve the robustness and applicability of future research in this area.